Relationship of Diabetes Mellitus Patient Satisfaction Survey with Prolanis Health Services - Oktavia, Santi; Sujiah, Sujiah; Andora, Novika; Maryuni, Sri (Global Health Science Group, 2024)
Diabetes mellitus is classified as a chronic disease that causes complications that must be prevented. One way to prevent complications is to try to maintain stable blood sugar levels in people with diabetes mellitus. Therefore, the government established the Chronic Disease Management Program (PROLANIS) through BPJS to provide services to maintain stable blood sugar. The aim of this research is the relationship between the Diabetes Mellitus Patient Satisfaction Survey and Prolanis Health Services at the Way Kandis Community Health Center.This research method uses a quantitative type of research with a cross sectional approach. The test used is chi square. The population in this study were 254 patients with diabetes mellitus and the sample in this study was 42 diabetes mellitus patients.Based on the results of univariate analysis, it is known that the majority of respondents said they were dissatisfied, amounting to 15 people (35.7%) and respondents who received prolanis health services which were not good, amounting to 25 respondents (59.5%). Based on the results of statistical tests, a p-value of 0.018 <0.05 was obtained, which means there is a relationship between the Diabetes Mellitus Patient Satisfaction Survey and Prolanis Health Services at the Way Kandis Community Health Center, Bandar Lampung. As input for community health center managers to improve health services as well as insight into the effectiveness of interactions with patients, and especially on satisfaction with the prolanis program for diabetes mellitus patients.